Production Of Crude Biopolymer From Bacteria In Drainage System - Talib, Azieda Abdul (2014)
This work focuses on the extraction of biopolymer from bacteria in relation to wastewater treatment, specifically in flocculation process. Three isolates of bacterial strain (WIR, WRA, WIA) which are able to produce biopolymers as flocculants were identified from industrial and residential drainage systems. These bacteria were identified as Bacillus megaterium BMRA, Bacillus megaterium BMIR and Bacillus subtilis BSIA through physiological characteristics (mucoid, slimy and ropy) and the partial sequences of their 16SrRNA. Crude biopolymers CWIR (industrial + residential) and CWRA (residential) were produced by Bacillus megaterium BMIR and BMRA while CWIA (industrial) was extracted from Bacillus subtilis BSIA. These bacteria produced their respective biopolymers at 40ºC given a two-day incubation period, with pH 7.0 ± 0.03. The crude biopolymers were recovered from the supernatant of the culture broth by ethanol precipitation and vacuum-dried in vacuum oven. CWIR, CWRA and CWIA contained 4.01%, 5.20% and 5.45% of protein respectively. Total sugar content in each biopolymer was 1.48% for CWIR, 1.65% for CWRA and 1.79% for CWIA. Elemental analyses showed that the CWIR obtained had 31.60% of C, 4.81% of H and 6.32% of N, while WRA contained 31.37% of C, 5.02% of H and 6.12% of N. WIA showed a composition comprising 31.25% of C, 4.88% of H and 5.69% of N. The molecular weight for each of the biopolymers CWIA, CWIR and CWRA was measured at 31.788 kDa, 55.344 kDa and 38.791 kDa respectively.